2015
DOI: 10.1098/rsfs.2014.0047
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry-specific surface adsorption of the barnacle settlement-inducing protein complex

Abstract: Gregarious settlement in barnacle larvae (cyprids) is induced by a contact pheromone, the settlement-inducing protein complex (SIPC). The SIPC has been identified both in the cuticle of adult barnacles and in the temporary adhesive secretion (footprint) of cyprids. Besides acting as a settlement inducer, the presence of the SIPC in footprints points to its additional involvement in the adhesion process. SIPC adsorption behaviour was therefore investigated on a series of self-assembled monolayers (SAMs) by surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 43 publications
0
24
1
1
Order By: Relevance
“…Using two different self-assembled monolayers (SAMs) to vary the surface chemistry, we demonstrate that both surface interactions and bulk swimming patterns vary with the surface chemistry. The surfaces were chosen since cyprids are known to interact very weakly with oligo(ethylene glycol) chains and more strongly with carboxylic acid groups (Andersson, Ekblad et al 2009, Aldred, Ekblad et al 2011, Petrone, Aldred et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Using two different self-assembled monolayers (SAMs) to vary the surface chemistry, we demonstrate that both surface interactions and bulk swimming patterns vary with the surface chemistry. The surfaces were chosen since cyprids are known to interact very weakly with oligo(ethylene glycol) chains and more strongly with carboxylic acid groups (Andersson, Ekblad et al 2009, Aldred, Ekblad et al 2011, Petrone, Aldred et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…In barnacle larvae, one protein, SIPC (settlement-inducing protein complex), is present in the larval temporary adhesive secretion and, therefore, plays a double role in settlement and adhesion. Petrone et al [4] report on the measurement of the adsorption behaviour of SIPC to various surfaces. The establishment of the bond for biological adhesives does indeed start with the adsorption of the adhesive biopolymers to the surface.…”
mentioning
confidence: 99%
“…Preliminary investigations of the adhesive properties of SIPC examined its involvement in temporary adhesion and found that although the protein shares significant sequence homology with a family of proteins that includes the α 2 -macroglobulins (which are blood complement protease inhibitors, functioning to inactivate proteolytic enzymes in immune responses), it was in actuality more comparable to fibrinogen (clotting factor I), which shares no sequence homology (Petrone et al, 2015). Surface plasmon resonance (SPR) was used to measure protein adsorption behavior of SIPC on self-assembled monolayers (SAMs) compared to both α 2 -macroglobulin and fibrinogen and found that SIPC behaved more similarly to fibrinogen (Petrone et al, 2015).…”
Section: Proteins Expressed In Higher Abundance In the 15°c Treatmentmentioning
confidence: 99%
“…Surface plasmon resonance (SPR) was used to measure protein adsorption behavior of SIPC on self-assembled monolayers (SAMs) compared to both α 2 -macroglobulin and fibrinogen and found that SIPC behaved more similarly to fibrinogen (Petrone et al, 2015). Thus, the authors determined that SIPC appears to behave as a 'sticky' type protein, which supports its role as a proposed temporary adhesive of barnacle larvae (Petrone et al, 2015). Since SIPC is also expressed during later developmental stages, it seems probably that these sticky characteristics may also serve an additional adhesive role in more mature barnacles.…”
Section: Proteins Expressed In Higher Abundance In the 15°c Treatmentmentioning
confidence: 99%
See 1 more Smart Citation